Experimental Analysis of Granular Material Flows Using the Technique of Digital Particle Image Velocimetry - SIELAMOWICZ, Irena (Engineering Transactions, 2005)
This paper presents the results of experiments of granular flows carried out for two configurations – in a plane model with vertical walls and in a wedge-shaped model. Both models were built of plexiglass and replicate the geometry of a silo. The flow processes of central and eccentric discharge were recorded by a high resolution camera (SensiCam) through the transparent walls of the models. PIV measurements allow to obtain the following data of the flow: the plug flow zone evolution, velocity magnitude contours, velocity fields, velocity distributions on certain levels in the models, traces of individual particles. Local deformations and stresses in the material may be also determined. The models were filled in a natural way through a pipe placed vertically in the symmetry axis above the models or through a sieve. In the case of the plane model, three cases of eccentric flows were investigated. Dynamic behaviour of the flowing materials recorded by the new measurement technique DPIV, commonly used in fluid mechanics, now applied for granular material flows, is analysed. Uniform and repeatable packing of the materials with no particle segregation was obtained. Three different grain types were used in the experiments (amaranthus, flax-seed and buckwheat). These grains represent different physical properties and exhibit the phenomenon of static electricity of the materials when flowing and sliding over plexiglass.